2009
DOI: 10.1007/s00018-009-0090-7
|View full text |Cite
|
Sign up to set email alerts
|

Reverse signaling using an inducible costimulator to enhance immunogenic function of dendritic cells

Abstract: A costimulatory signal from an inducible costimulator (ICOS) of T cells plays a critical role in immunological homeostasis. This study shows that the interaction of ICOSIg and its ligand (ICOSL) on mouse bone marrow-derived dendritic cells (DCs) induces a p38-MAPK dependent elevation of interleukin 6 (IL-6). It also enhances phagocytosis and the antigen-presentation function of DCs in vitro, further favoring cell-mediated immunity in vivo. As seen for other types of costimulator molecules expressed in the T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
29
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 42 publications
(88 reference statements)
5
29
1
Order By: Relevance
“…These results are quite different from those reported in regard to mouse bone marrow-derived DCs by Tang et al (35) showing that, in the absence of other stimuli, B7h triggering induced partial maturation of iDCs. This is mediated by a p38 MAPK-dependent signal with selective augmentation of IL-6 secretion; a similar effect was detected by Orabona et al (5) by using CD28-Fc to trigger B7.1 and B7.2.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These results are quite different from those reported in regard to mouse bone marrow-derived DCs by Tang et al (35) showing that, in the absence of other stimuli, B7h triggering induced partial maturation of iDCs. This is mediated by a p38 MAPK-dependent signal with selective augmentation of IL-6 secretion; a similar effect was detected by Orabona et al (5) by using CD28-Fc to trigger B7.1 and B7.2.…”
Section: Discussioncontrasting
confidence: 99%
“…This is mediated by a p38 MAPK-dependent signal with selective augmentation of IL-6 secretion; a similar effect was detected by Orabona et al (5) by using CD28-Fc to trigger B7.1 and B7.2. Moreover, in these murine DCs, B7h triggering increased expression of CD80, CD83, CD86, and MHC-II, phagocytosis, and Ag presentation to CD4 + Th cells, and supported their polarization to Th1 cells (35). However, the differences between these data on mice and our results on human DCs are not surprising in light of the several different functions that ICOS displays in the two species (25)(26)(27)(28)(29)(30)(31).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Moreover, we found that B7h triggering in human DCs increases the secretion of IL-23 (which is involved in Th17 expansion and survival) and supports Th17 cell activity (18). Finally, ICOS triggering in T cells (which is blocked by ICOS-Fc) is involved in the differentiation of both Tregs and Th17 cells (17,(31)(32)(33); however, its support of Treg differentiation prevails in the tumor environment (34,35).…”
Section: Discussionmentioning
confidence: 80%
“…Additionally, a CD4 + b 2 -microglobulin-dependent NOD T cell subset has been suggested to play a role in regulation diabetogenic BDC2.5 NOD CD4 + T cells (transferred to NOD.scid) via IFN-g-dependent modulation of host APCs (45 (34). It also remains a possibility that ICOS on CD4 + 24ab type II NKT cells could modulate DCs by binding ICOS-L on these cells, as it was reported that ligation of ICOS-L influenced the function of bone marrow-derived DCs (46). PD-1 and its ligands PD-L1 and PD-L2 play an important role in the control of T cell activation and peripheral tolerance (47).…”
Section: Discussionmentioning
confidence: 99%